Role and prognostic value of oncostatin M and its receptor OSMR in acute myeloid leukemia, myeloproliferative neoplasms and non-hematological malignancies - Lévesque, Jean-Pierre; Bisht, Kavita; Alexander, Kylie A.; Winkler, Ingrid G. (Frontiers in Oncology, 2025)
The oncostatin M receptor (OSMR) has recently emerged as an adverse prognostic factor in acute myeloid leukemia (AML) and several non-hematological malignancies. In this perspective, we discuss how oncostatin M (OSM) and its receptor OSMR regulate tumor cells as well as mesenchymal and endothelial cells, which are key components of hematopoietic stem cell and tumor stem cell niches, and how these mechanisms could explain the poor prognosis associated with high expression of OSM and OSMR in hematological and non-hematological malignancies.